Inspired by Harold Conklin - Gerard A. Persoon; Jan van der Ploeg; Merlijn van Weerd (Revue d'ethnoécologie)
Harold C. Conklin (1926-2016) is without doubt one of the key figures in ethnobotany and environmental anthropology. His work is admired for, among other qualities, its precision and its level of « fine description ». In particular, his pioneering studies on shifting cultivation have changed the general perspective on this way of land use. His Ethnographic Atlas of Ifugao (1980) is still a landmark of ethnographic fieldwork, combining a wide range of methods, including sophisticated cartography. The focus of this atlas was on the culture of Ifugao farmers in their home area in the Cordillera Mountains on the island of Luzon in the Philippines. In recent decades, thousands of Ifugao farmers have left their home area and migrated eastwards to the Sierra Madre Mountains in the northeastern part of Luzon, across Cagayan Valley. They have done so for various reasons but land shortage is certainly one of them. In the foothills of the Sierra Madre, accessible arable land became available after large-scale commercial logging operations. In this article we will draw attention to the relevance of Conklin’s work before describing how the Ifugao farmers, with their extensive knowledge and experience, have been able to turn this new area into a highly productive environment, combining wet rice fields with upland agriculture. The research is based on fieldwork that was done over several years with Filipino, Dutch and other international students in the context of a long-standing cooperation project between Isabela State University in the Philippines and Leiden University (Netherlands).